The Development of Bacteriophage Resistance in Vibrio alginolyticus Depends on a Complex Metabolic Adaptation Strategy - Dimitrios Skliros; Panos G. Kalatzis; Chrysanthi Kalloniati; Fotios Komaitis; Sokratis Papathanasiou; Evangelia D. Kouri; Michael K. Udvardi; Constantina Kokkari; Pantelis Katharios; Emmanouil Flemetakis (Viruses, 2021)
Lytic bacteriophages have been well documented to play a pivotal role in microbial ecology due to their complex interactions with bacterial species, especially in aquatic habitats. Although the use of phages as antimicrobial agents, known as phage therapy, in the aquatic environment has been increasing, recent research has revealed drawbacks due to the development of phage-resistant strains among Gram-negative species. Acquired phage resistance in marine Vibrios has been proven to be a very complicated process utilizing biochemical, metabolic, and molecular adaptation strategies. The results of our multi-omics approach, incorporating transcriptome and metabolome analyses of Vibrio alginolyticus phage-resistant strains, corroborate this prospect. Our results provide insights into phage-tolerant strains diminishing the expression of phage receptors ompF, lamB, and btuB. The same pattern was observed for genes encoding natural nutrient channels, such as rbsA, ptsG, tryP, livH, lysE, and hisp, meaning that the cell needs to readjust its biochemistry to achieve phage resistance. The results showed reprogramming of bacterial metabolism by transcript regulations in key-metabolic pathways, such as the tricarboxylic acid cycle (TCA) and lysine biosynthesis, as well as the content of intracellular metabolites belonging to processes that could also significantly affect the cell physiology. Finally, SNP analysis in resistant strains revealed no evidence of amino acid alterations in the studied putative bacterial phage receptors, but several SNPs were detected in genes involved in transcriptional regulation. This phenomenon appears to be a phage-specific, fine-tuned metabolic engineering, imposed by the different phage genera the bacteria have interacted with, updating the role of lytic phages in microbial marine ecology.